A Review on Technique in Managing Oil Palm Plantation towards a Digitalized Online 3D Application - Mat, Ruzinoor Che; ., Norani Nordin; ., Shahrul Azmi Mohd Yusof (Information Management and Business Review, 2013)
The oil palm industry has been well known as the backbone in Malaysian agriculture and still maintain as the main commodity exports. The research on oil palm industry has been growing gradually by utilizing various methods and technology to solve the problem in managing oil palm plantation. The aim of this paper is to review the technique in managing oil palm plantation towards a digitalized online 3D application. Various problems and techniques on managing oil palm plantation has been reviewed which involving various technology such as GIS, GPS, DBMS and hyperspectral. It was found that monitoring the characteristic of oil palm plantation is beneficial and important to oil palm planters. The new online 3D application for oil palm plantation management has a potential of assisting oil palm managers in making a decision, visualizing their plantation in online 3D environment, and managing their plantation effectively.